Penelitian Evaluasi: Kajian Evaluasi Kinerja Institusi aspek Kinerja Penelitian - Syahrir, Syahrir; Tjalla, Awaluddin; Indrajit, Richardus Eko (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
The purpose of this article is to analyze the evaluation of the institutional evaluation of research aspects. The results of the analysis on several articles that are spoken, performance evaluation, evaluation of several basic factors in evaluating the impact of research for decision making on the development of research proposal performance, theory of institutional evaluation research concepts, research team trails, research management, research impact, research mobilization and research participant groups.